(untitled) (World Bulletin of Public Health, 2022)
A review of the literature is presented and the "global burden of glaucoma in the gerontial population" is shown in different regions and populations based on a large-scale analysis. Ways to improve the disease prevention system are described and recommended. Scientific materials are important in determining preventive research and practices.